Analisis Pembandingan Pola Keanekaragaman Pisang Introduksi Berdasarkan Penanda Fenotipik dengan Penanda RAPD dan Pendugaan Korelasi antara Keduanya terhadap Komposisi Genomiknya - Hanik Rohmah Robi'ah; Sobir Sobir; Memen Surahman (Indonesia Society of Agronomy (PERAGI) and Department of Agronomy and Horticulture, Faculty of Agriculture, IPB University, Bogor, Indonesia, 2005)
Banana accessions introduced from INIBAP Transit Center (ITC) have been studied their diversity revealed on phenotypic and RAPD markers. Both of them showed different clustering pattern and not fit to genomic composition. In order to know fitness level of clustering pattern both of them, comparison analysis have done to their similarity coefficient matrix, and followed by partial correlation analysis among phenotypic traits, and genomic composition. The comparison analysis resulting very poor correlation (r = 0.491). Partially correlation analysis among traits, DNA profile, and Musa genomic composition at 95-99% confidence revealed only OPA-18 line 2 related to accessions possessed pure